Evaluating economic impacts of marketing agreements in a differentiated U.S. beef industry - Doumit, Katherine Margaret (My University, 2025)
Understanding the impact of value-based pricing methods on beef cattle quality, as well as differentiating the impact of high- and low-quality beef across the supply chain, has become increasingly important with the rise in high-quality cattle over the past decade. The shift towards alternative marketing agreements (AMAs) has heightened concerns over market transparency and price discovery, emphasizing the need to understand the long-term impact of these marketing methods on the industry. This thesis first evaluates the influence of value-based pricing methods, specifically formula and negotiated grid pricing, on the percentage of cattle grading Choice and Prime. Using a quality index model, economic factors impacting cattle quality grading are evaluated. Findings indicate that increased use of AMAs has substantially shifted the quality dynamics of the beef industry, with a 0.94% increase in cattle grading Choice for every 1% increase in formula and grid priced cattle. Building on these results, the economic impacts of supply shifts in high-quality beef are assessed across four levels of the beef supply chain – retail, wholesale, slaughter, farm – under scenarios of reduced formula and grid pricing. Since the dramatic improvement in beef quality and shift in fed cattle marketing methods, a study analyzing the impacts on a differentiated market has not been completed. This research uses an equilibrium displacement model to evaluate the impacts of a negative shock to high-quality wholesale beef supply resulting from an increased use of cash negotiated trade, as proposed policy in policy discussions. Findings indicate an increase in price and decrease quantity for high-quality wholesale and retail beef while price declines and quantity increases for low-quality wholesale and retail beef. Aggregate slaughter and feeder cattle producers experience declines in both price and quantity. Findings from this study show a strong association between formula and grid pricing methods and high-quality beef production. Policies mandating increased cash-negotiated trade, which would diminish the use of formula and grid pricing, are shown to reduce demand for cattle from producers, ultimately leading to lower prices received by them. By adopting a heterogenous market perspective, this study highlights the differential impacts of AMAs, providing stakeholders with crucial insights into the valuation and policy implications of AMAs in the evolving beef industry.
Keywords: Beef; Cattle marketing; Value-based pricing; Beef quality